The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26227034
|View full text |Cite
|
Sign up to set email alerts
|

Three New Phthalide Glycosides from the Rhizomes of Cnidium officinale and Their Recovery Effect on Damaged Otic Hair Cells in Zebrafish

Abstract: The extract from Cnidium officinale rhizomes was shown in a prior experiment to markedly recover otic hair cells in zebrafish damaged by neomycin. The current study was brought about to identify the principal metabolite. Column chromatography using octadecyl SiO2 and SiO2 was performed to isolate the major metabolites from the active fraction. The chemical structures were resolved on the basis of spectroscopic data, including NMR, IR, MS, and circular dichroism (CD) data. The isolated phthalide glycosides were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Neomycin is known to cause hair cell death in zebrafish [ 55 , 56 , 57 , 58 ], much like it does in HEI-OC1 cells. Various natural products have been reported to increase the number of hair cells in neomycin-damaged zebrafish larvae [ 59 , 60 ]. Therefore, the effect of TS treatment on the recovery of neomycin-induced hair cell loss was evaluated in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Neomycin is known to cause hair cell death in zebrafish [ 55 , 56 , 57 , 58 ], much like it does in HEI-OC1 cells. Various natural products have been reported to increase the number of hair cells in neomycin-damaged zebrafish larvae [ 59 , 60 ]. Therefore, the effect of TS treatment on the recovery of neomycin-induced hair cell loss was evaluated in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 99%
“…, naringin (4), hesperidin (5), neohesperidin (6), liquiritigenin (7), glycyrrhizin (8), and 6-shogaol (9).…”
Section: Optimization Of Lc-ms/ms Mrm Conditionsmentioning
confidence: 99%
“…Nine herbal medicines have been reported to have various biological effects, for example, anti-inflammatory, antioxidant, anticancer, antitumor, antidiabetes, antiaging, anti-obesity, neuroprotective, and antibacterial activities [6][7][8][9][10][11][12][13][14]. Recently, a study on the safety of a single administration of GHT was reported by An et al [4], but few studies on the biological activity have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The structural characterizations of phthalides are accomplished frequently by the analysis of Infrared (IR) spectroscopy, mass spectrometry (MS), GC coupled to selective mass detectors (GC‐MS) and high‐resolution mass spectrometry (HR‐MS), high‐performance liquid chromatography (HPLC), and 1D and 2D Nuclear Magnetic Resonance (NMR), electronic circular dichroism (ECD) and X‐ray crystallographic data, or frequently a combination of them has been applied [80–87] …”
Section: Introductionmentioning
confidence: 99%